Statement of Peer Review - Muhammad Mahabat Khan; Mohammad Javed Hyder; Muhammad Irfan; Manzar Masud (Engineering Proceedings)
In submitting conference proceedings to Engineering Proceedings, the volume editors of the proceedings certify to the publisher that all papers published in this volume have been subjected to peer review administered by the volume editors [...]